How We Decide in Moral Situations. (15th July 2014) - Kaspar, David
Abstract: The role normative ethics has in guiding action is unclear. Once moral theorists hoped that they could devise a decision procedure that would enable agents to solve difficult moral problems. Repeated attacks by anti-theorists seemingly dashed this hope. Although the dispute between moral theorists and anti-theorists rages no longer, no decisive victor has emerged. To determine how we ought to make moral decisions, I argue, we must first examine how we do decide in moral situations. Intuitionism correctly captures the essence of the moral element in such situations, finding itself located somewhere between moral theory and anti-theory. In order that intuitionism may constitute an improvement over predecessors in normative ethics we must proceed with awareness of the limits imposed by the still dominant framework of modern moral theory. I argue that the deliberatively open system of intuitionism, interlocked in practice with prudential considerations, allows us to constructively move normative ethics beyond those limits.